The Effectiveness of Predict-Explain-Observe-Discuss-Explain (PEODE) Based Laboratory Work Activities on Pre-Service Science Teachers’ Science Process Skills - Bayram, Hale; Coştu, Fatma (Mimbar Sekolah Dasar, 2021)
This research aims at investigating the effectiveness of the Predict-Explain-Observe-Discuss-Explain (PEODE) based laboratory work activities on pre-service science teachers’ science process skills. A quasi-experimental research model with pre- and post-test via control group was employed in the research. The semi-experimental study was based on 46 pre-service science teachers enrolled in the primary Science Education Program a state university. In the research, randomly selected two groups were used, one experimental group (EG; n = 22) and one control group (CG; n = 24). While the control group participated in traditional laboratory activities work, the experimental group took part in the PEODE-based laboratory work activities. Laboratory activities were carried out in both groups for a total of 9 weeks, two hours a week. Science process skills test (SPST) measuring five different scientific process skills were presented to them as pre- and post-test in order to assess pre-service science teachers’ science process skills. The test scores were analyzed quantitatively with a statistical analysis program. At the end of the research, while there was no significant differences total score of the SPST, significant statistical differences were found between the experimental and control groups in "Making Operational Comments" and "Designing the Research" sub-skills.